Estimating money laundering risks: an application to business sectors in the Netherlands - Ferwerda, Joras (European journal on criminal policy and research, 2019)
Current money laundering policies often rely on the same prescribed instruments for many business sectors. For ‘risk based’ policies, however, it is important to know in which business sectors money laundering risks are relatively higher. This paper builds upon work conducted as part of Identifying and Assessing the Risk of Money Laundering in Europe (IARM) project and focuses on money laundering risk assessment in the Netherlands. In this paper, we discuss theoretically and empirically how these risks can be estimated and we present results based on data regarding business sectors in the Netherlands. The used risk factors include data on organised crime investments, beneficial owners, and confidential information from the Dutch Tax Office on anomalies in tax declarations by companies. Our results indicate that casinos, hotels, and the art and entertainment sector have the highest money laundering risks in the Netherlands.